A structural equation model analyzing the relationship model on perception students toward mathematics / Siti Fairus Mokhtar - Mokhtar, Siti Fairus (2015)
Student performance in universities is as highly concern to government as it represents the competency towards real world situations. The aim of this study is to develop the model on perception students toward Business Mathematics course. A questionnaire was distributed to students in Kedah area. Structural Equation Modeling (SEM) approach was used to access the model fit and to test the hypothesis. The latent constructs are interest, usefulness of mathematics, role of the teacher, peers and attitude related to the performance students toward Business Mathematics course. The result shows that all latent constructs are positive correlation.